(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Neutropenia has been defined to be classified into transient and chronic forms based upon duration and acquired or congenital forms. Chronic neutropenia is considered as congenital, cyclic, autoimmune and idiopathic categorizes, where congenital and cyclic categories are hereditary forms of neutropenia, but the idiopathic and autoimmune are known as acquired neutropenia. In the present review, we focus highly on the genetic subtypes of non-syndromic congenital neutropenia and therapeutic strategies regarding to recent evidence. All aspects of molecular pathogenesis and biology have not been clarified so far; therefore, further in-depth understanding of the molecular mechanisms is needed to reveal roles of molecular mechanisms, and pathways involved in the development of congenital neutropenia and to provide a basis for achieving novel therapeutic strategies.